Slope intercept form is y = mx + b
So if you start with 9x - 7y = -7, the first thing you need to do is move the 9x to the other side of the equation by subtracting it from both sides.
9x - 7y = -7
-9x -9x
Now you have -7y = -9x -7
For the equation to be in slope intercept form now you should divide every term by the number in front of your y. In this case divide every term by -7
-<u>7y</u> = <u>-9x</u> <u>-7</u>
-7 -7 -7
That leaves you with: y = 9x/7 + 1
Answer:
sqrt(5)*sqrt(5)=5.
Step-by-step explanation:
Answer:
1. k
2. 12r-20
3. 10n-13
4. -6x
5. -11r
6. 4x+11
Step-by-step explanation:
The answer to this question is 6
Solution,
y = -x-4......(i)
3x + y =- 16.......(ii)
Now,
Substituting the value of y in equation (ii)
or, 3x + (-x-4)= -16
or,3x - x - 4 = -16
or, 2x= -16 +4
or, x = -12/2
: x = -6
Then,
Substituting the value of x in (i) equation;
or,y= -(-6) - 4
or,y= 6 - 4
: y =2